Character Education and Socio-Emotional Development of Early Childhood - Irfa Nur Amalia; Fajar Indarsih; Fatqurhohman Fatqurhohman (Ihsan Cahaya Pustaka, 2025)
Character education in early childhood serves as the foundation for personality development, morality, and socio-emotional competence. This study employs a qualitative approach with a critical and systematic literature review to analyze the concepts, values, mechanisms, and impacts of character education on children’s socio-emotional development. Findings indicate that character education is effectively fostered through modeling, habituation, guidance, supervision, and meaningful play activities. Core values such as honesty, discipline, tolerance, independence, religiosity, and nationalism underpin emotional regulation, empathy, social skills, and value-based decision-making. Families as primary environments, early childhood education institutions (PAUD) as systemic support, structured curricula, and communities as social experience spaces synergistically promote holistic character development. In the digital era, healthy digital literacy and active guidance from parents and teachers are essential to ensure technology supports, rather than hinders, value internalization. This study emphasizes the critical role of character education in shaping adaptive, prosocial, and integrity-driven young children.